A revolutionary history of interwar India: violence, image, voice and text - Maclean, Kama (Oxford University Press, 2015)
This study draws on new evidence to deliver a fresh perspective on the ambitions, ideologies and practices of the Hindustan Socialist Republican Association or Army (HSRA), the revolutionary party formed by Chandrashekhar Azad and Bhagat Singh, inspired by transnational anti-imperial dissent. The book offers an account of the activities of the north Indian revolutionaries who advocated the use of political violence against the British; and considers the impact of their actions on the mainstream nationalism of the Indian National Congress.
Includes bibliographical references and index. - Description based on online resource; title from home page (viewed on April 21, 2015)
Keywords: India -- History -- 20th century; India -- History -- Autonomy and independence movements; Revolutionär; Britisch-Indien